Border carbon adjustments and alternative measures for the EU ETS: An evaluation - Roland Ismer; Karsten Neuhoff; Alice Pirlot (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
As part of its Green Deal, the European Commission is considering the introduction of border carbon adjustments and alternative measures. The measures, which would primarily apply to basic materials like steel and cement, pursue a double objective: they are aimed at enhancing the effectiveness of carbon pricing for the transition to climate neutrality but also at avoiding carbon leakage risks. When implementing carbon adjustment mechanisms and alternative measures, various design options might be considered to reform the EU Emissions Trading Scheme (EU ETS). In this paper, we have decided to focus on three main models, which help to highlight the main differences between the available options. Under the first model, importers of basic materials would be required to surrender carbon allowances at the level of a product benchmark or, where lower, at the verified level of foreign carbon intensity. In parallel, allocation of free allowances would be phased out. Under the second model, a symmetric adjustment mechanism for exports and imports would be adopted, including refund to exporters for the carbon costs incurred on basic materials embodied in products. Finally, under the third model, the EU ETS would be complemented with a climate contribution charged for materials sold in the European Union (EU) at the product benchmark level related to the carbon intensity of each material. The free allowance allocation regime would then be modified to be directly linked to the volume of material production at the product benchmark level. In order to contribute to the current policy debate, we evaluate for each of these three models, their legality, coherence with EU climate objectives, effectiveness in carbon leakage prevention, potential international implications, as well as their administrative complexity and compliance costs.
Keywords: F18; K33; L61; Q58; 330; Carbon pricing; Climate policy; International trade; WTO